Advanced sports nutrition - Benardot, Dan (Human Kinetics, 2012)
Advanced Sports Nutrition helped thousands of athletes apply the most effective and cutting-edge strategies for optimal fueling and performance. Now this best-seller returns, updated with the latest research, topics, and innovations in sports nutrition. Far beyond the typical food pyramid formula, Advanced Sports Nutrition offers serious strategies for serious athletes. This comprehensive guide includes the latest nutrition concepts for athletes in any sport. The best conditioning programs and technical instruction are beneficial only if your body is properly fueled and ready to operate at peak efficiency. With Advanced Sports Nutrition, Second Edition, you can be assured that when you are ready to push the limits of training and competition, your body is, too.